10 anos de balanço sobre Ciência, Tecnologia e Inovação no Brasil - Camargo, Daniel Ferraz de (Universidade Federal de São Carlos, 2023)
This study examines Science, Technology, and Innovation (STI) policies in Brazil from 2012 to 2022, addressing the importance of this sector for sustainable development. Over this decade, three successive governments implemented different STI strategies, impacting the national scientific and technological landscape. The Dilma Rousseff government stood out for significant investments, while Michel Temer's government emphasized efficiency and decentralization. The Jair Bolsonaro government adopted an austerity stance, reducing support for the sector. Documentary analysis covers STI investment data and innovation indicators. It is concluded that Brazil faces significant challenges, such as the need to increase investment, improve infrastructure, and promote an innovation culture to drive scientific and technological development.
10 years of review regarding Science, Technology and Innovation in Brazil
Keywords: Ciência, tecnologia e inovação; Brasil; Políticas de C, T & I; Desenvolvimento sustentável; Science, technology and innovation; Brazil; S, T&I policies; Sustainable development; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO